Technical Note: Confirming the prescribed angle of CT localizer radiographs and c‐arm projection acquisitions. Issue 2 (20th January 2016) - Szczykutowicz, Timothy P.; Labby, Zacariah E.; Rubert, Nicholas; Wallace, Charles
Abstract : Purpose: Accurate CT radiograph angle is not usually important in diagnostic CT. However, there are applications in radiation oncology and interventional radiology in which the orientation of the x‐ray source and detector with respect to the patient is clinically important. The authors present a method for measuring the accuracy of the tube/detector assembly with respect to the prescribed tube/detector position for CT localizer, fluoroscopic, and general radiograph imaging using diagnostic, mobile, and c‐arm based CT systems. Methods: A mathematical expression relating the x‐ray projection of two metal BBs is related to gantry angle. Measurement of the BBs at a prescribed gantry (i.e., c‐arm) angle can be obtained and using this relation the prescribed versus actual gantry angle compared. No special service mode or proprietary information is required, only access to projection images is required. Projection images are available in CT via CT localizer radiographs and in the interventional setting via fluorography. Results: The technique was demonstrated on two systems, a mobile CT scanner and a diagnostic CT scanner. The results confirmed a known issue with the mobile scanner and accurately described the CT localizer angle of the diagnostic system tested. Conclusions: This method can be used to quantify gantry angle, which is important when projection images are used for procedure guidance, such as in brachytherapy and interventional radiology applications.